DNA Methylation Adjusts the Specificity of Memories Depending on the Learning Context and Promotes Relearning in Honeybees - Biergans, Stephanie D.; Claudianos, Charles; Reinhard, Judith; Galizia, C. G. (Frontiers in Molecular Neuroscience, 2016)
The activity of the epigenetic writers DNA methyltransferases (Dnmts) after olfactory reward conditioning is important for both stimulus-specific long-term memory (LTM) formation and extinction. It, however, remains unknown which components of memory formation Dnmts regulate (e.g. associative vs. non-associative) and in what context (e.g. varying training conditions). Here we address these aspects in order to clarify the role of Dnmt-mediated DNA methylation in memory formation. We used a pharmacological Dnmt inhibitor and classical appetitive conditioning in the honeybee Apis mellifera, a well characterized model for classical conditioning. We quantified the effect of DNA methylation on naïve odour and sugar responses, and on responses following olfactory reward conditioning. We show that (1) Dnmts do not influence naïve odour or sugar responses, (2) Dnmts do not affect the learning of new stimuli, but (3) Dnmts influence odour-coding, i.e. 'correct' (stimulus-specific) LTM formation. Particularly, Dnmts reduce memory specificity when experience is low (one-trial training), and increase memory specificity when experience is high (multiple-trial training), generating an ecologically more useful response to learning. (4) In reversal learning conditions, Dnmts are involved in regulating both excitatory (re-acquisition) and inhibitory (forgetting) processes.